A self-adhesive polymer modified asphalt composite anti-root waterproofing membrane and preparation method thereof
By combining modified styrene butadiene rubber and epoxy resin microcapsules, the waterproof roll material is given flame retardant and antibacterial properties, and the water resistance and oxidation resistance are improved by modified microcapsules, which solves the problems of insufficient root puncture resistance, unstable flame retardancy and poor antibacterial properties of the waterproof roll material when facing plant root puncture and high humidity environment, and achieves excellent anti-root performance, stable flame retardancy and significantly improved antibacterial properties.
Patent Information
- Application Number
- CN202411484158.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-23
- Publication Date
- 2025-04-29
- Estimated Expiration
- 2044-10-23
AI Technical Summary
When facing plant root puncture and high humidity environments, existing waterproof coils have problems such as insufficient root puncture resistance, unstable flame retardancy, and poor antibacterial properties, resulting in water leakage and material deterioration.
By modifying styrene butadiene rubber and epoxy resin microcapsules, the styrene butadiene rubber is imparted with flame retardant and antibacterial properties, and its water resistance and oxidation resistance are enhanced by modified microcapsules. Combining root resistors and light calcium carbonate, a polymer-modified asphalt layer with self-healing, flame retardant and antibacterial properties is formed.
The excellent anti-root performance, stable flame retardancy and significantly improved antibacterial properties of the waterproof coil are achieved, extending the service life of the material and improving its durability in high humidity environments.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The invention relates to the field of waterproofing coiled materials, and in particular to a self-adhesive polymer modified asphalt composite anti-root waterproofing coiled material and a preparation method thereof. Background Art
[0002] As people's living standards continue to improve, building gardens on roofs and planting flowers, vegetables and green plants can not only beautify and improve the living environment, but also increase people's rest and entertainment places. However, the growth of plant roots on the roof will pierce waterproof materials such as roof waterproof membranes, causing water to leak into the house. At present, self-adhesive polymer modified asphalt composite waterproof membranes with root penetration resistance are widely studied.
[0003] Previous studies have used epoxy resin microcapsules to improve the self-healing ability of waterproof membranes. The epoxy resin microcapsules are made of urea-formaldehyde resin as the capsule wall and E-51 epoxy resin as the capsule core. When the membrane is damaged by root thorns or external forces, the epoxy resin inside can be released and repair the damaged parts after curing. Urea-formaldehyde resin has poor water resistance and will also oxidize and degrade under long-term effects of light, heat, oxygen, etc. The waterproof membranes used on the roof will be directly affected by rain, snow, freezing, light, high temperature, etc. Therefore, epoxy resin microcapsules with urea-formaldehyde resin as the wall material are limited in the use of waterproof membranes.
[0004] The asphalt used in the self-adhesive polymer modified asphalt composite waterproofing membrane is a flammable material. Styrene butadiene rubber (SBR) and asphalt have good compatibility. In the prior art, styrene butadiene rubber is often used to modify the low-temperature resistance of asphalt, but styrene butadiene rubber itself does not have flame retardancy. Directly adding small molecule flame retardants with excellent flame retardancy to improve the flame retardancy of the self-adhesive polymer modified asphalt composite waterproofing membrane has the problems of easy migration failure and poor compatibility with asphalt, styrene butadiene rubber, etc., and therefore cannot maintain stable flame retardancy.
[0005] With the continuous improvement of science and technology, high humidity environment will cause bacteria and mold to grow. The growing bacteria and mold will not only affect the appearance, but also make the waterproof membrane fragile and easy to damage, thereby shortening the service life of the waterproof membrane. Therefore, higher requirements are put forward for the antibacterial property of the waterproof membrane. There are many cases in the prior art of directly adding antibacterial agents to improve the antibacterial property of the waterproof membrane, but the antibacterial property of the waterproof membrane still cannot meet the use requirements.
[0006] Therefore, it is of practical significance to find a suitable method to improve the water resistance and oxidation resistance of the wall material of epoxy resin microcapsules, and then graft flame retardants and antibacterial agents into styrene butadiene rubber molecules to give styrene butadiene rubber flame retardancy and antibacterial properties, and then use styrene butadiene rubber with flame retardancy and antibacterial properties and epoxy resin microcapsules with improved water resistance and oxidation resistance to modify asphalt, so as to obtain self-healing, flame retardancy, antibacterial properties and other better self-adhesive polymer modified asphalt composite waterproof membrane with root penetration resistance. Summary of the invention
[0007] In order to solve the above technical problems, the present invention provides a self-adhesive polymer modified asphalt composite anti-root waterproofing membrane and a preparation method thereof.
[0008] The purpose of the present invention can be achieved through the following technical solutions:
[0009] A self-adhesive polymer modified asphalt composite anti-root waterproofing membrane comprises an isolation membrane layer, a polymer modified asphalt layer, a base layer, a polymer modified asphalt layer, and an isolation membrane layer which are sequentially arranged from top to bottom; the isolation membrane layer is a polyethylene membrane layer, and the base layer is a HDPE membrane layer;
[0010] The polymer modified asphalt layer comprises the following raw materials in parts by weight: 48-52 parts of petroleum asphalt, 12-14 parts of aromatic oil, 3-5 parts of SBS, 13-15 parts of modified styrene-butadiene rubber, 5-7 parts of polyisobutylene, 4-6 parts of modified microcapsules, 1-2 parts of root inhibitor, 11-13 parts of light calcium carbonate and 0.3-0.5 parts of silane coupling agent; the root inhibitor is m-chloropropiophenone; the polyisobutylene is highly active polyisobutylene; the silane coupling agent is 10-alkenyl undecyl trimethoxy silane;
[0011] The preparation of the self-adhesive polymer modified asphalt composite anti-root waterproofing membrane comprises the following steps:
[0012] Step S1: firstly, heating the petroleum asphalt to 200-210° C. under stirring, then adding aromatic oil, SBS, and modified styrene-butadiene rubber and continuing stirring for 1.5-2.0 hours, cooling to 90-100° C., then adding polyisobutylene, modified microcapsules, light calcium carbonate, and silane coupling agent and stirring for 1-1.5 hours, and finally adding a root inhibitor and stirring for 0.5-1.0 hours to obtain a polymer modified asphalt mixture;
[0013] Step S2: coating the polymer modified asphalt mixture on the upper and lower surfaces of the tread base to form two upper and lower polymer modified asphalt layers, and then covering the outer surfaces of the upper and lower polymer modified asphalt layers with a polyethylene film to form two isolation film layers to obtain a self-adhesive polymer modified asphalt composite anti-root waterproof membrane; the thickness of the two polymer modified asphalt layers is the same and is both 3-5 mm.
[0014] The modified microcapsules are prepared by the following steps:
[0015] Step A1: drying epoxy resin microcapsules (supplier: Wuxi Huilong Electronic Materials Co., Ltd.) at 75-80°C for 4-6 hours to obtain dried microcapsules; adding silane coupling agent 1 to deionized water, stirring for 20-25 minutes, adjusting the pH to 6.8-7.2, adding dried microcapsules, heating to 80-85°C, stirring for 1-1.5 hours, washing with ethanol and filtering, and then drying at 45-55°C for 26-28 hours to obtain amino-containing microcapsules;
[0016] Further, the dosage ratio of silane coupling agent 1, deionized water, and dried microcapsules is 5-6 g: 100-110 mL: 10-12 g, the volume fraction of ethanol is 95%, and the silane coupling agent 1 is KH-540;
[0017] During the reaction of step A1, the silanol obtained after the hydrolysis of KH-540 treats the surface of the microcapsule wall material and is grafted with the microcapsule wall material to obtain an amino-containing microcapsule;
[0018] Step A2: adding 4-dimethylaminobenzoic acid and 6-chloro-1-hexene to n-propanol, heating to 110-120° C., stirring and reacting at a constant temperature for 6-7 hours to obtain a quaternary ammonium salt product; stirring and mixing the quaternary ammonium salt product, distilled water, and ethanol, heating to 80-85° C., adding nano-montmorillonite, stirring at 900-1000 r / min for 3-4 hours, and obtaining modified montmorillonite;
[0019] Further, the dosage ratio of 4-dimethylaminobenzoic acid, 6-chloro-1-hexene and n-propanol is 0.1 mol: 0.1-0.13 mol: 65-75 mL; the dosage ratio of quaternary ammonium salt product, nano-montmorillonite, distilled water and ethanol is 2.8-3.3 g: 1 g: 20-30 mL: 20-30 mL, and the volume fraction of ethanol is 95%;
[0020] During the reaction of step A2, the tertiary amine of 4-dimethylaminobenzoic acid reacts with 6-chloro-1-hexene to generate a quaternary ammonium salt product containing a terminal carbon-carbon double bond and a carboxyl group; the quaternary ammonium cation in the quaternary ammonium salt product modifies the montmorillonite to obtain a modified montmorillonite containing a terminal carbon-carbon double bond and a carboxyl group;
[0021] Step A3: Add modified montmorillonite to DMF, add thionyl chloride under stirring, reflux and stir at 50-60° C. for 4-5 hours to obtain an acyl chloride product; stir and mix the amino-containing microcapsules, potassium carbonate and dimethyl sulfoxide to obtain a mixed solution 1, then add the acyl chloride product to dimethyl sulfoxide and stir and mix to obtain a mixed solution 2, add the mixed solution 2 dropwise to the mixed solution 1 in an ice-water bath, raise the temperature to 45-50° C. after the addition is complete, stir and react at a constant temperature for 8-10 hours, and distill under reduced pressure to obtain an amide product;
[0022] Further, the dosage ratio of modified montmorillonite, DMF and thionyl chloride is 5-6g: 25-35mL: 0.5-0.7mol; the dosage ratio of amino-containing microcapsules, potassium carbonate and dimethyl sulfoxide is 6-7g: 0.3-0.5mol: 55-65mL; the dosage ratio of acyl chloride product and dimethyl sulfoxide is 8-10g: 45-55mL; the dosage ratio of mixed solution 1 and mixed solution 2 is 70-80mL: 60-70mL;
[0023] During the reaction of step A3, the carboxyl groups in the modified montmorillonite react with thionyl chloride to generate an acyl chloride product; the acyl chloride product reacts with the amino-containing microcapsules to generate an amide product containing a terminal carbon-carbon double bond;
[0024] Step A4: stirring the amide product, 2,6-bis(tert-butyl)-4-(mercaptomethyl)phenol, DMF and 4-dimethylaminopyridine under ultraviolet light for 20-30 minutes, and drying to obtain modified microcapsules;
[0025] Further, the usage ratio of the amide product, 2,6-bis(tert-butyl)-4-(mercaptomethyl)phenol, DMF, and 4-dimethylaminopyridine is 5-6 g:13-14 g:80-90 mL:0.5-0.7 g, and the power of the ultraviolet light is 100-150 W;
[0026] During the reaction of step A4, the terminal carbon-carbon double bond contained in the amide product undergoes a click reaction with the thiol group of 2,6-bis(tert-butyl)-4-(mercaptomethyl)phenol under ultraviolet light to obtain modified microcapsules.
[0027] The modified styrene-butadiene rubber is prepared by the following steps:
[0028] Step B1: adding styrene butadiene rubber to cyclohexane and stirring for 30-40 minutes to obtain a styrene butadiene rubber solution; then adding meta-chloroperbenzoic acid to tetrahydrofuran and stirring for 10-15 minutes to obtain a meta-chloroperbenzoic acid solution; then heating the styrene butadiene rubber solution to 35-40° C., then dropping the meta-chloroperbenzoic acid solution into the styrene butadiene rubber solution through a constant pressure dropping funnel, stirring and reacting for 1.5-2.0 hours after the dropwise addition is completed, adding sodium hydroxide solution and stirring to separate the aqueous phase until the pH of the organic phase is 7-8, and then flocculating the organic phase with anhydrous ethanol and tetrahydrofuran three times respectively, and drying to obtain epoxidized emulsion polystyrene butadiene rubber;
[0029] Further, the dosage ratio of styrene-butadiene rubber and cyclohexane is 10-15 g: 100-150 mL; the dosage ratio of meta-chloroperbenzoic acid and tetrahydrofuran is 34.5-35.5 g: 100-110 mL; the dosage ratio of styrene-butadiene rubber solution and meta-chloroperbenzoic acid solution is 110-120 mL: 12-14 mL; the mass fraction of sodium hydroxide solution is 10-15%;
[0030] During the reaction of step B1, the carbon-carbon double bonds in the styrene-butadiene rubber are partially oxidized by m-chloroperbenzoic acid to form epoxy groups, thereby obtaining epoxidized emulsion-polymerized styrene-butadiene rubber;
[0031] Step B2: Stirring and mixing the epoxidized emulsion polystyrene-butadiene rubber and DOPO, heating to 85-90°C, stirring for 10-15 minutes, adding triphenylphosphine, and heating to 140-150°C, maintaining for 3.5-4 hours to obtain a reaction solution, cooling the reaction solution to room temperature, adding ethyl acetate, standing for 48-50 hours, and filtering to obtain a hydroxyl product;
[0032] Further, the usage ratio of epoxidized emulsion polybutadiene styrene rubber, DOPO, triphenylphosphine and ethyl acetate is 21-23 g: 15-17 g: 0.05-0.07 mol: 150-160 mL;
[0033] During the reaction of step B2, the epoxy group in the epoxidized emulsion polystyrene-butadiene rubber reacts with DOPO, and the DOPO structure is grafted onto the styrene-butadiene rubber to obtain a hydroxyl product;
[0034] Step B3: Stirring and mixing the hydroxyl product, pyridine, triethylamine and dimethyl sulfoxide to obtain a mixed solution a; adding sorbyl chloride to dimethyl sulfoxide to obtain a mixed solution b; adding the mixed solution b dropwise to the mixed solution a in an ice water bath; after the addition is complete, heating to 40-45° C., stirring at a constant temperature for 8-10 hours, and then heating to 100-110° C., continuing stirring for 1-2 hours, and distilling under reduced pressure to obtain modified styrene-butadiene rubber;
[0035] Further, the dosage ratio of the hydroxyl product, pyridine, triethylamine and dimethyl sulfoxide is 26-28 g: 18-20 mL: 30-35 mL: 100-110 mL; the dosage ratio of sorbyl chloride and dimethyl sulfoxide is 15-17 g: 40-50 mL; the dosage ratio of the mixed solution a and the mixed solution b is 17-19 mL: 6-8 mL;
[0036] During the reaction of step B3, the hydroxyl product reacts with sorbic acid chloride to graft the sorbate group into the styrene-butadiene rubber to obtain a modified styrene-butadiene rubber containing a DOPO structure and a sorbate group, so that the styrene-butadiene rubber itself has the flame retardancy of DOPO and the antibacterial property of the sorbate group.
[0037] Beneficial effects of the invention: The invention discloses a self-adhesive polymer modified asphalt composite anti-root waterproof membrane, comprising an isolation membrane layer, a polymer modified asphalt layer, a tread base layer, a polymer modified asphalt layer, and an isolation membrane layer which are arranged in sequence from top to bottom; the tread base layer is a HDPE membrane layer, which has a physical root barrier effect; the polymer modified asphalt layer is prepared from raw materials such as petroleum asphalt, aromatic oil, SBS, modified styrene-butadiene rubber, polyisobutylene, modified microcapsules, and root barrier agents; the root barrier agent added in the polymer modified asphalt layer has a chemical root barrier effect, which cooperates with the physical root barrier effect of the tread base layer to enable the waterproof membrane to have excellent anti-root performance.
[0038] The synthesized modified microcapsules are obtained by modifying the wall material of epoxy resin microcapsules with epoxy resin as the core material and urea-formaldehyde resin as the wall material, and grafting functional structures such as nano-montmorillonite, hindered phenol and thioether groups into the wall material urea-formaldehyde resin. After the nano-montmorillonite is organically modified and grafted with urea-formaldehyde resin, its compatibility in urea-formaldehyde resin is greatly improved, which is beneficial to improving the water resistance and thermal stability of urea-formaldehyde resin; hindered phenol reacts with peroxide radicals to generate hydroperoxide, which terminates the free radical reaction in the oxidative degradation process of the polymer, and thioether groups can reduce and decompose hydroperoxide, hindered phenol and thioether groups produce intramolecular synergistic effects, significantly improving the antioxidant properties of urea-formaldehyde resin; after the water resistance, thermal stability and antioxidant properties of the modified microcapsules are improved, they are more suitable for waterproof membranes and are more conducive to improving the self-healing properties of waterproof membranes.
[0039] The synthesized modified styrene butadiene rubber is obtained by reacting the epoxy group of epoxidized emulsion polystyrene butadiene rubber with DOPO and sorbic acid chloride, grafting DOPO and sorbic acid ester groups into styrene butadiene rubber, giving styrene butadiene rubber flame retardancy and antibacterial properties. The DOPO structure can dehydrate and degrade the burning surface to form a carbon layer when the matrix burns, and the phosphorus-containing derivatives produced at the same time cover the surface, isolating the combustible gas and heat transfer, forming a physical shield to prevent the combustion from continuing; compared with sorbic acid, which is difficult to enter microbial cells because it is easy to form an ion state under neutral and alkaline conditions, sorbic acid esters are less affected by acidity and alkalinity and have a stronger affinity with microbial membranes, making it easier to penetrate into microbial cells, so they have stronger antibacterial properties. Because the modified styrene butadiene rubber itself has strong flame retardancy and antibacterial properties, the flame retardancy and antibacterial properties of the waterproof roll prepared by mixing it with asphalt and the like are also improved. DETAILED DESCRIPTION
[0040] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0041] Example 1
[0042] A modified microcapsule, the preparation of which comprises the following steps:
[0043] Step A1: drying epoxy resin microcapsules (supplier: Wuxi Huilong Electronic Materials Co., Ltd.) at 75°C for 4 hours to obtain dried microcapsules; adding KH-540 to deionized water, stirring for 20 minutes, adjusting the pH to 6.8, adding dried microcapsules, heating to 80°C, stirring for 1 hour, washing with ethanol and filtering, and then drying at 45°C for 26 hours to obtain amino-containing microcapsules; the dosage ratio of KH-540, deionized water, and dried microcapsules is 5g:100mL:10g, and the volume fraction of ethanol is 95%;
[0044] Step A2: adding 4-dimethylaminobenzoic acid and 6-chloro-1-hexene to n-propanol, heating to 110° C., stirring and reacting at constant temperature for 6 hours to obtain a quaternary ammonium salt product; stirring and mixing the quaternary ammonium salt product, distilled water, and ethanol, heating to 80° C., adding nano-montmorillonite, and stirring at 900 r / min for 3 hours to obtain modified montmorillonite; the amount ratio of 4-dimethylaminobenzoic acid, 6-chloro-1-hexene, and n-propanol is 0.1 mol: 0.1 mol: 65 mL; the amount ratio of the quaternary ammonium salt product, nano-montmorillonite, distilled water, and ethanol is 2.8 g: 1 g: 20 mL: 20 mL, and the volume fraction of ethanol is 95%;
[0045] Step A3: Add modified montmorillonite to DMF, add dichlorothionyl under stirring, and reflux and stir at 50°C for 4 hours to obtain an acyl chloride product; stir and mix the amino-containing microcapsules, potassium carbonate and dimethyl sulfoxide to obtain a mixed solution 1, then add the acyl chloride product to dimethyl sulfoxide and stir and mix to obtain a mixed solution 2, and dropwise add the mixed solution 2 to the mixed solution 1 under an ice-water bath. After the dropwise addition is completed, the temperature is raised to 45°C, stirred and reacted at a constant temperature for 8 hours, and distilled under reduced pressure to obtain an amide product; the amount ratio of modified montmorillonite, DMF and dichlorothionyl is 5g:25mL:0.5mol; the amount ratio of amino-containing microcapsules, potassium carbonate and dimethyl sulfoxide is 6g:0.3mol:55mL; the amount ratio of acyl chloride product and dimethyl sulfoxide is 8g:45mL; the amount ratio of mixed solution 1 to mixed solution 2 is 70mL:60mL;
[0046] Step A4: Stir the amide product, 2,6-bis(tert-butyl)-4-(mercaptomethyl)phenol, DMF and 4-dimethylaminopyridine under ultraviolet light for 20 minutes and dry to obtain modified microcapsules; the amount ratio of the amide product, 2,6-bis(tert-butyl)-4-(mercaptomethyl)phenol, DMF and 4-dimethylaminopyridine is 5g:13g:80mL:0.5g, and the power of the ultraviolet light is 100W.
[0047] Example 2
[0048] A modified microcapsule, the preparation of which comprises the following steps:
[0049] Step A1: drying epoxy resin microcapsules (supplier: Wuxi Huilong Electronic Materials Co., Ltd.) at 78°C for 5 hours to obtain dried microcapsules; adding KH-540 to deionized water, stirring for 23 minutes, adjusting the pH to 7.0, adding dried microcapsules, heating to 83°C, stirring for 1.3 hours, washing with ethanol and filtering, and then drying at 50°C for 27 hours to obtain amino-containing microcapsules; the dosage ratio of KH-540, deionized water, and dried microcapsules is 5.5g:105mL:11g, and the volume fraction of ethanol is 95%;
[0050] Step A2: Add 4-dimethylaminobenzoic acid and 6-chloro-1-hexene to n-propanol, heat to 115° C., and stir at constant temperature for 6.5 hours to obtain a quaternary ammonium salt product; stir and mix the quaternary ammonium salt product, distilled water, and ethanol, heat to 83° C., add nano-montmorillonite, and stir at 900 r / min for 3.5 hours to obtain modified montmorillonite; the amount ratio of 4-dimethylaminobenzoic acid, 6-chloro-1-hexene, and n-propanol is 0.1 mol: 0.12 mol: 70 mL; the amount ratio of the quaternary ammonium salt product, nano-montmorillonite, distilled water, and ethanol is 3.0 g: 1 g: 25 mL: 25 mL, and the volume fraction of ethanol is 95%;
[0051] Step A3: Add modified montmorillonite to DMF, add dichlorothionyl under stirring, and reflux and stir at 55°C for 4.5h to obtain an acyl chloride product; stir and mix the amino-containing microcapsules, potassium carbonate and dimethyl sulfoxide to obtain a mixed solution 1, then add the acyl chloride product to dimethyl sulfoxide and stir and mix to obtain a mixed solution 2, and dropwise add the mixed solution 2 to the mixed solution 1 under an ice-water bath. After the dropwise addition is completed, the mixture is heated to 47°C, stirred and reacted at a constant temperature for 9h, and distilled under reduced pressure to obtain an amide product; the amount ratio of modified montmorillonite, DMF and dichlorothionyl is 5.5g:30mL:0.6mol; the amount ratio of amino-containing microcapsules, potassium carbonate and dimethyl sulfoxide is 6.5g:0.4mol:60mL; the amount ratio of acyl chloride product and dimethyl sulfoxide is 9g:50mL; the amount ratio of mixed solution 1 to mixed solution 2 is 75mL:65mL;
[0052] Step A4: Stir the amide product, 2,6-bis(tert-butyl)-4-(mercaptomethyl)phenol, DMF and 4-dimethylaminopyridine under ultraviolet light for 25 minutes and dry to obtain modified microcapsules; the amount ratio of the amide product, 2,6-bis(tert-butyl)-4-(mercaptomethyl)phenol, DMF and 4-dimethylaminopyridine is 5.5g:13.5g:85mL:0.6g, and the power of the ultraviolet light is 120W.
[0053] Example 3
[0054] A modified microcapsule, the preparation of which comprises the following steps:
[0055] Step A1: drying epoxy resin microcapsules (supplier: Wuxi Huilong Electronic Materials Co., Ltd.) at 80°C for 6 hours to obtain dried microcapsules; adding KH-540 to deionized water, stirring for 25 minutes, adjusting the pH to 7.2, adding dried microcapsules, heating to 85°C, stirring for 1.5 hours, washing with ethanol and filtering, and then drying at 55°C for 28 hours to obtain amino-containing microcapsules; the dosage ratio of KH-540, deionized water, and dried microcapsules is 6g:110mL:12g, and the volume fraction of ethanol is 95%;
[0056] Step A2: adding 4-dimethylaminobenzoic acid and 6-chloro-1-hexene to n-propanol, heating to 120° C., stirring and reacting at constant temperature for 7 hours to obtain a quaternary ammonium salt product; stirring and mixing the quaternary ammonium salt product, distilled water, and ethanol, heating to 85° C., adding nano-montmorillonite, and stirring at 1000 r / min for 4 hours to obtain modified montmorillonite; the amount ratio of 4-dimethylaminobenzoic acid, 6-chloro-1-hexene, and n-propanol is 0.1 mol: 0.13 mol: 75 mL; the amount ratio of the quaternary ammonium salt product, nano-montmorillonite, distilled water, and ethanol is 3.3 g: 1 g: 30 mL: 30 mL, and the volume fraction of ethanol is 95%;
[0057] Step A3: Add modified montmorillonite to DMF, add dichlorothionyl under stirring, and reflux and stir at 60°C for 5h to obtain an acyl chloride product; stir and mix the amino-containing microcapsules, potassium carbonate and dimethyl sulfoxide to obtain a mixed solution 1, then add the acyl chloride product to dimethyl sulfoxide and stir and mix to obtain a mixed solution 2, and dropwise add the mixed solution 2 to the mixed solution 1 under an ice-water bath. After the dropwise addition is completed, the mixture is heated to 50°C, stirred and reacted at a constant temperature for 10h, and distilled under reduced pressure to obtain an amide product; the amount ratio of modified montmorillonite, DMF and dichlorothionyl is 6g:35mL:0.7mol; the amount ratio of amino-containing microcapsules, potassium carbonate and dimethyl sulfoxide is 7g:0.5mol:65mL; the amount ratio of acyl chloride product and dimethyl sulfoxide is 10g:55mL; the amount ratio of mixed solution 1 to mixed solution 2 is 80mL:70mL;
[0058] Step A4: Stir the amide product, 2,6-bis(tert-butyl)-4-(mercaptomethyl)phenol, DMF and 4-dimethylaminopyridine under ultraviolet light for 30 minutes and dry to obtain modified microcapsules; the amount ratio of the amide product, 2,6-bis(tert-butyl)-4-(mercaptomethyl)phenol, DMF and 4-dimethylaminopyridine is 6g:14g:90mL:0.7g, and the power of the ultraviolet light is 150W.
[0059] Example 4
[0060] A modified styrene-butadiene rubber, the preparation of which comprises the following steps:
[0061] Step B1: Add styrene-butadiene rubber to cyclohexane and stir for 30 minutes to obtain a styrene-butadiene rubber solution; then add meta-chloroperbenzoic acid to tetrahydrofuran and stir for 10 minutes to obtain a meta-chloroperbenzoic acid solution; then heat the styrene-butadiene rubber solution to 35°C, then drop the meta-chloroperbenzoic acid solution into the styrene-butadiene rubber solution through a constant pressure dropping funnel, stir and react for 1.5 hours after the dropwise addition is complete, add sodium hydroxide solution and stir to separate the aqueous phase until the pH of the organic phase is 7, then flocculate the organic phase with anhydrous ethanol and tetrahydrofuran three times respectively, and then dry to obtain epoxidized emulsion polystyrene-butadiene rubber; the dosage ratio of styrene-butadiene rubber to cyclohexane is 10g:100mL; the dosage ratio of meta-chloroperbenzoic acid to tetrahydrofuran is 34.5g:100mL; the dosage ratio of styrene-butadiene rubber solution to meta-chloroperbenzoic acid solution is 110mL:12mL; the mass fraction of the sodium hydroxide solution is 10%;
[0062] Step B2: Stirring and mixing the epoxidized emulsion polystyrene butadiene rubber and DOPO and heating to 85°C, adding triphenylphosphine after continuing stirring for 10 minutes, and continuing to heat to 140°C and maintaining for 3.5 hours to obtain a reaction solution, cooling the reaction solution to room temperature, adding ethyl acetate, standing for 48 hours, and filtering to obtain a hydroxyl product; the amount ratio of the epoxidized emulsion polystyrene butadiene rubber, DOPO, triphenylphosphine and ethyl acetate is 21g:15g:0.05mol:150mL;
[0063] Step B3: The hydroxyl product, pyridine, triethylamine and dimethyl sulfoxide are stirred and mixed to obtain a mixed solution a; sorboyl chloride is added to dimethyl sulfoxide to obtain a mixed solution b, and the mixed solution b is added dropwise to the mixed solution a in an ice-water bath. After the addition is completed, the temperature is raised to 40°C, and the reaction is stirred at a constant temperature for 8 hours, and then the temperature is raised to 100°C, and the stirring is continued for 1 hour, and the modified styrene-butadiene rubber is obtained. The amount ratio of the hydroxyl product, pyridine, triethylamine and dimethyl sulfoxide is 26g:18mL:30mL:100mL; the amount ratio of sorboyl chloride and dimethyl sulfoxide is 15g:40mL; the amount ratio of the mixed solution a and the mixed solution b is 17mL:6mL.
[0064] Example 5
[0065] A modified styrene-butadiene rubber, the preparation of which comprises the following steps:
[0066] Step B1: Add styrene butadiene rubber to cyclohexane and stir for 35 minutes to obtain a styrene butadiene rubber solution; then add meta-chloroperbenzoic acid to tetrahydrofuran and stir for 13 minutes to obtain a meta-chloroperbenzoic acid solution; then heat the styrene butadiene rubber solution to 37°C, then drop the meta-chloroperbenzoic acid solution into the styrene butadiene rubber solution through a constant pressure dropping funnel, stir and react for 1.8 hours after the dropwise addition is complete, add sodium hydroxide solution and stir to separate the aqueous phase until the pH of the organic phase is 7, then flocculate the organic phase with anhydrous ethanol and tetrahydrofuran three times respectively, and then dry to obtain epoxidized emulsion polystyrene butadiene rubber; the dosage ratio of styrene butadiene rubber to cyclohexane is 13g:130mL; the dosage ratio of meta-chloroperbenzoic acid to tetrahydrofuran is 35.0g:105mL; the dosage ratio of styrene butadiene rubber solution to meta-chloroperbenzoic acid solution is 115mL:13mL; the mass fraction of the sodium hydroxide solution is 13%;
[0067] Step B2: Stirring and mixing the epoxidized emulsion polystyrene butadiene rubber and DOPO and heating to 88°C, adding triphenylphosphine after continuing stirring for 13 minutes, and continuing to heat to 145°C and maintaining for 3.7 hours to obtain a reaction solution, cooling the reaction solution to room temperature, adding ethyl acetate, standing for 49 hours, and filtering to obtain a hydroxyl product; the amount ratio of the epoxidized emulsion polystyrene butadiene rubber, DOPO, triphenylphosphine and ethyl acetate is 22g:16g:0.06mol:155mL;
[0068] Step B3: The hydroxyl product, pyridine, triethylamine and dimethyl sulfoxide are stirred and mixed to obtain a mixed solution a; sorboyl chloride is added to dimethyl sulfoxide to obtain a mixed solution b, and the mixed solution b is added dropwise to the mixed solution a in an ice-water bath. After the addition is completed, the temperature is raised to 43° C., and the mixture is stirred at a constant temperature for 9 hours, and then the temperature is raised to 105° C., and stirring is continued for 1.5 hours. The modified styrene-butadiene rubber is obtained by distillation under reduced pressure; the amount ratio of the hydroxyl product, pyridine, triethylamine and dimethyl sulfoxide is 27 g: 19 mL: 33 mL: 105 mL; the amount ratio of sorboyl chloride and dimethyl sulfoxide is 16 g: 45 mL; the amount ratio of the mixed solution a and the mixed solution b is 18 mL: 7 mL.
[0069] Example 6
[0070] A modified styrene-butadiene rubber, the preparation of which comprises the following steps:
[0071] Step B1: Add styrene-butadiene rubber to cyclohexane and stir for 40 minutes to obtain a styrene-butadiene rubber solution; then add meta-chloroperbenzoic acid to tetrahydrofuran and stir for 15 minutes to obtain a meta-chloroperbenzoic acid solution; then heat the styrene-butadiene rubber solution to 40°C, then drop the meta-chloroperbenzoic acid solution into the styrene-butadiene rubber solution through a constant pressure dropping funnel, stir and react for 2.0 hours after the dropwise addition is complete, add sodium hydroxide solution and stir to separate the aqueous phase until the pH of the organic phase is 8, then flocculate the organic phase with anhydrous ethanol and tetrahydrofuran three times respectively, and then dry to obtain epoxidized emulsion polystyrene-butadiene rubber; the dosage ratio of styrene-butadiene rubber to cyclohexane is 15g:150mL; the dosage ratio of meta-chloroperbenzoic acid to tetrahydrofuran is 35.5g:110mL; the dosage ratio of styrene-butadiene rubber solution to meta-chloroperbenzoic acid solution is 120mL:14mL; the mass fraction of the sodium hydroxide solution is 15%;
[0072] Step B2: Stirring and mixing the epoxidized emulsion polystyrene butadiene rubber and DOPO and heating to 90°C, adding triphenylphosphine after continuing stirring for 15 minutes, and continuing heating to 150°C and maintaining for 4 hours to obtain a reaction solution, cooling the reaction solution to room temperature, adding ethyl acetate, standing for 50 hours, and filtering to obtain a hydroxyl product; the amount ratio of the epoxidized emulsion polystyrene butadiene rubber, DOPO, triphenylphosphine and ethyl acetate is 23g:17g:0.07mol:160mL;
[0073] Step B3: The hydroxyl product, pyridine, triethylamine and dimethyl sulfoxide are stirred and mixed to obtain a mixed solution a; sorboyl chloride is added to dimethyl sulfoxide to obtain a mixed solution b, and the mixed solution b is added dropwise to the mixed solution a in an ice-water bath. After the addition is completed, the temperature is raised to 45° C., and the mixture is stirred at a constant temperature for 10 hours, and then the temperature is raised to 110° C., and the stirring is continued for 2 hours, and the modified styrene-butadiene rubber is obtained by distillation under reduced pressure; the amount ratio of the hydroxyl product, pyridine, triethylamine and dimethyl sulfoxide is 28 g: 20 mL: 35 mL: 110 mL; the amount ratio of sorboyl chloride and dimethyl sulfoxide is 17 g: 50 mL; the amount ratio of the mixed solution a and the mixed solution b is 19 mL: 8 mL.
[0074] Example 7
[0075] A self-adhesive polymer modified asphalt composite anti-root waterproofing coiled material, comprising an isolation membrane layer, a polymer modified asphalt layer, a tire base layer, a polymer modified asphalt layer, and an isolation membrane layer, which are arranged in sequence from top to bottom; the isolation membrane layer is a polyethylene membrane layer, and the tire base layer is a HDPE membrane layer; the polymer modified asphalt layer comprises the following raw materials in parts by weight: 48 parts of 70# petroleum asphalt, 12 parts of aromatic oil DYA-02, 3 parts of SBS, 13 parts of modified styrene-butadiene rubber, 5 parts of polyisobutylene, 4 parts of modified microcapsules, 1 part of root inhibitor, 11 parts of light calcium carbonate, and 0.3 parts of silane coupling agent; the root inhibitor is m-chlorophenylacetone, the polyisobutylene is a highly active polyisobutylene, and the silane coupling agent is 10-alkenyl undecyl trimethoxysilane;
[0076] The preparation of the self-adhesive polymer modified asphalt composite anti-root waterproofing membrane comprises the following steps:
[0077] Step S1: firstly, heating 70# petroleum asphalt to 200°C under stirring, then adding aromatic oil DYA-02, SBS, and the modified styrene-butadiene rubber obtained in Example 4, and continuing stirring for 1.5 hours, cooling to 90°C, then adding polyisobutylene, the modified microcapsules obtained in Example 1, light calcium carbonate and silane coupling agent, stirring for 1 hour, and finally adding a root inhibitor and stirring for 0.5 hours to obtain a polymer modified asphalt mixture;
[0078] Step S2: Coat the polymer-modified asphalt mixture on the upper and lower surfaces of the HDPE geomembrane (supplier: Tai'an Zerui Geotechnical Materials Co., Ltd.) to form two upper and lower polymer-modified asphalt layers, and then cover the outer surfaces of the upper and lower polymer-modified asphalt layers with a polyethylene film (supplier: Shandong Dexuda Geotechnical Materials Co., Ltd.) to form two isolation film layers to obtain a self-adhesive polymer-modified asphalt composite anti-root waterproof membrane; the thickness of the two polymer-modified asphalt layers is the same and is both 3 mm.
[0079] Example 8
[0080] A self-adhesive polymer modified asphalt composite anti-root waterproofing coiled material, comprising an isolation membrane layer, a polymer modified asphalt layer, a tire base layer, a polymer modified asphalt layer, and an isolation membrane layer, which are arranged in sequence from top to bottom; the isolation membrane layer is a polyethylene membrane layer, and the tire base layer is a HDPE membrane layer; the polymer modified asphalt layer comprises the following raw materials in parts by weight: 50 parts of 70# petroleum asphalt, 13 parts of aromatic oil DYA-02, 4 parts of SBS, 14 parts of modified styrene-butadiene rubber, 6 parts of polyisobutylene, 5 parts of modified microcapsules, 1.5 parts of root inhibitor, 12 parts of light calcium carbonate, and 0.4 parts of silane coupling agent; the root inhibitor is m-chlorophenylacetone, the polyisobutylene is a highly active polyisobutylene, and the silane coupling agent is 10-alkenyl undecyl trimethoxysilane;
[0081] The preparation of the self-adhesive polymer modified asphalt composite anti-root waterproofing membrane comprises the following steps:
[0082] Step S1: firstly, heating 70# petroleum asphalt to 205°C under stirring, then adding aromatic oil DYA-02, SBS, and the modified styrene-butadiene rubber obtained in Example 5 and continuing stirring for 1.8h, cooling to 95°C, then adding polyisobutylene, the modified microcapsules obtained in Example 2, light calcium carbonate and silane coupling agent and stirring for 1.3h, and finally adding root inhibitor and stirring for 0.8h to obtain a polymer modified asphalt mixture;
[0083] Step S2: Coat the polymer-modified asphalt mixture on the upper and lower surfaces of the HDPE geomembrane (supplier: Tai'an Zerui Geotechnical Materials Co., Ltd.) to form two upper and lower polymer-modified asphalt layers, and then cover the polyethylene film (supplier: Shandong Dexuda Geotechnical Materials Co., Ltd.) on the outer surfaces of the upper and lower polymer-modified asphalt layers to form two isolation film layers to obtain a self-adhesive polymer-modified asphalt composite anti-root waterproof membrane; the thickness of the two polymer-modified asphalt layers is the same and is both 4 mm.
[0084] Example 9
[0085] A self-adhesive polymer modified asphalt composite anti-root waterproofing coiled material, comprising an isolation membrane layer, a polymer modified asphalt layer, a tire base layer, a polymer modified asphalt layer, and an isolation membrane layer, which are sequentially arranged from top to bottom; the isolation membrane layer is a polyethylene membrane layer, and the tire base layer is a HDPE membrane layer; the polymer modified asphalt layer comprises the following raw materials in parts by weight: 52 parts of 90# petroleum asphalt, 14 parts of aromatic oil DYA-02, 5 parts of SBS, 15 parts of modified styrene-butadiene rubber obtained in Example 3, 7 parts of polyisobutylene, 6 parts of modified microcapsules obtained in Example 6, 2 parts of root inhibitor, 13 parts of light calcium carbonate, and 0.5 parts of silane coupling agent; the root inhibitor is m-chlorophenylacetone, the polyisobutylene is highly active polyisobutylene, and the silane coupling agent is 10-alkenyl undecyl trimethoxysilane;
[0086] The preparation of the self-adhesive polymer modified asphalt composite anti-root waterproofing membrane comprises the following steps:
[0087] Step S1: firstly, heating 90# petroleum asphalt to 210°C under stirring, then adding aromatic oil DYA-02, SBS, and modified styrene-butadiene rubber and continuing stirring for 2.0 hours, cooling to 100°C, then adding polyisobutylene, modified microcapsules, light calcium carbonate, and silane coupling agent and stirring for 1.5 hours, and finally adding root inhibitor and stirring for 1.0 hour to obtain polymer modified asphalt mixture;
[0088] Step S2: Coat the polymer-modified asphalt mixture on the upper and lower surfaces of the HDPE geomembrane (supplier: Tai'an Zerui Geotechnical Materials Co., Ltd.) to form two upper and lower polymer-modified asphalt layers, and then cover the outer surfaces of the upper and lower polymer-modified asphalt layers with a polyethylene film (supplier: Shandong Dexuda Geotechnical Materials Co., Ltd.) to form two isolation film layers to obtain a self-adhesive polymer-modified asphalt composite anti-root waterproof membrane; the thickness of the two polymer-modified asphalt layers is the same and is both 5 mm.
[0089] Comparative Example 1
[0090] Compared with Example 9, the modified microcapsules are replaced with the amide product obtained in step A3, that is, hindered phenol and thioether are not introduced, and the rest is exactly the same as Example 9 to obtain a self-adhesive polymer modified asphalt composite anti-root waterproof membrane.
[0091] Comparative Example 2
[0092] Compared with Example 9, the 2,6-bis(tert-butyl)-4-(mercaptomethyl)phenol in step A4 of the modified microcapsule preparation process is replaced with n-dodecyl mercaptan, that is, no hindered phenol is introduced, only the thioether group is introduced, and the rest is exactly the same as Example 9, to obtain a self-adhesive polymer modified asphalt composite anti-root waterproof membrane.
[0093] Comparative Example 3
[0094] Compared with Example 9, the modified microcapsules were replaced with modified microcapsules 1, that is, nano-montmorillonite was not introduced, and the rest was exactly the same as Example 9 to obtain a self-adhesive polymer modified asphalt composite anti-root waterproof membrane.
[0095] Preparation process of modified microcapsule 1: Step 1, drying epoxy resin microcapsules (supplier: Wuxi Huilong Electronic Materials Co., Ltd.) at 90°C for 8h to obtain dried microcapsules 1 for standby use; adding 10-alkenyl undecyl trimethoxy silane to deionized water, then adding acetic acid solution, stirring for 15min, adjusting the pH to neutral, adding dried microcapsules 1, heating to 85°C, stirring for 1.5h, washing with ethanol and filtering, and then drying at 50°C for 26h to obtain microcapsules containing terminal carbon-carbon double bonds; 10-alkenyl undecyl trimethoxy silane, deionized water, acetic acid solution, dried microcapsules The dosage ratio of capsule 1 is 6g:100mL:20mL:12g, the mass fraction of acetic acid solution is 40%, and the volume fraction of ethanol is 95%; step 2, stirring microcapsules containing terminal carbon-carbon double bonds, 2,6-bis(tert-butyl)-4-(mercaptomethyl)phenol, DMF, and 4-dimethylaminopyridine under ultraviolet light for 30 minutes, and drying to obtain modified microcapsules 1; the dosage ratio of microcapsules containing terminal carbon-carbon double bonds, 2,6-bis(tert-butyl)-4-(mercaptomethyl)phenol, DMF, and 4-dimethylaminopyridine is 4g:12g:70L:0.4g, and the power of ultraviolet light is 150W.
[0096] Comparative Example 4
[0097] Compared with Example 9, the modified styrene butadiene rubber is replaced with modified styrene butadiene rubber 1, that is, no sorbate group is introduced, only DOPO is introduced, and the rest is exactly the same as Example 9, to obtain a self-adhesive polymer modified asphalt composite anti-root waterproof membrane.
[0098] The preparation process of modified styrene butadiene rubber 1 is as follows: epoxidized emulsion polystyrene butadiene rubber (the preparation method is the same as the preparation process of epoxidized emulsion polystyrene butadiene rubber used in Example 9) and DOPO are stirred and mixed and the temperature is raised to 90°C. After continuing to stir for 15 minutes, triphenylphosphine is added, and the temperature is continued to be raised to 150°C and maintained for 4 hours to obtain reaction solution 1. After cooling reaction solution 1 to room temperature, ethyl acetate is added, and after standing for 50 hours, the modified styrene butadiene rubber 1 is obtained. The amount ratio of epoxidized emulsion polystyrene butadiene rubber, DOPO, triphenylphosphine and ethyl acetate is 23g:17g:0.07mol:160mL.
[0099] Comparative Example 5
[0100] Compared with Example 9, the modified styrene butadiene rubber is replaced with modified styrene butadiene rubber 2, that is, DOPO is not introduced, and only sorbate groups are introduced. The rest is exactly the same as Example 9, and a self-adhesive polymer modified asphalt composite anti-root waterproof membrane is obtained.
[0101] The preparation process of modified styrene butadiene rubber 2 is as follows: in a nitrogen atmosphere, sorbic acid is added to toluene, the temperature is raised to 50°C with stirring, pyridine is added, and epoxidized emulsion polystyrene butadiene rubber (the preparation method is the same as the preparation process of epoxidized emulsion polystyrene butadiene rubber used in Example 9) is added, the reaction is stirred for 10 hours, and then the temperature is raised to 110°C and stirred for 2 hours to obtain modified styrene butadiene rubber 2; the amount ratio of sorbic acid, toluene, pyridine and epoxidized emulsion polystyrene butadiene rubber is 15g:300mL:0.09mol:100g.
[0102] The self-adhesive polymer modified asphalt composite anti-root waterproof membrane prepared by the present invention is further tested for its effect, and the test results are as follows.
[0103] In order to test the self-adhesive polymer modified asphalt composite anti-root waterproof membrane prepared by the present invention, Escherichia coli and Staphylococcus aureus were used as the test strains to determine the antibacterial rate of the waterproof membranes obtained in Examples 7-9 and Comparative Examples 1-5; referring to the relevant requirements in GB18242-2008 "Elastomer modified asphalt waterproof membrane" and GB / T2408-2021 "Horizontal and vertical methods for determination of combustion performance of plastics", an oxygen index tester (YG-813 type) was used to perform limiting oxygen index test and flame retardant grade test on the waterproof membranes obtained in Examples 7-9 and Comparative Examples 1-5; the waterproof membranes obtained in Examples 7-9 and Comparative Examples 1-5 were placed at room temperature and immersed in distilled water for 24 hours, and the healing rate after immersion was determined; the waterproof membranes obtained in Examples 7-9 and Comparative Examples 1-5 were placed at 80°C for 3 hours, and the healing rate after high heat treatment was determined; the waterproof membranes obtained in Examples 7-9 and Comparative Examples 1-5 were placed in an ultraviolet radiation with an intensity of 0.89W / m 2 After treatment at 25°C and aging time of 48h, the healing rate after photo-oxidation was measured; the results are recorded in Table 1;
[0104] Self-repairing ability test method: Through the indentation loading test, the load ratio of the indentation loading test before and after the healing of the waterproof membrane obtained in Examples 7-9 and Comparative Examples 1-5 is measured, and the ratio is used as the healing rate to indicate the self-repairing ability of the waterproof membrane. The greater the healing rate, the stronger the self-repairing ability;
[0105] Healing rate (%) = load of indentation loading test after healing (kN) / load of indentation loading test before healing (kN) * 100.
[0106]
[0107] According to the data in Table 1, the self-adhesive polymer modified asphalt composite anti-root waterproofing membrane of the present invention has excellent self-repairing ability, antibacterial property and flame retardancy. It can be seen from Example 9 compared with Comparative Example 1 that only nano-montmorillonite is introduced into the epoxy resin microcapsule wall material, and hindered phenol and thioether group are not introduced. The antioxidant property of the modified microcapsule is greatly reduced, and the healing rate of the waterproofing membrane decreases more after photo-oxidation treatment, and the self-repairing ability decreases more. It can be seen from Example 9 compared with Comparative Example 2 that only nano-montmorillonite and thioether group are introduced into the epoxy resin microcapsule wall material, and hindered phenol is not introduced. The antioxidant property of the modified microcapsule is reduced, and the healing rate of the waterproofing membrane decreases after photo-oxidation treatment, and the self-repairing ability decreases. It can be seen from Example 9 compared with Comparative Example 3 that only hindered phenol and thioether group are introduced, and nano-montmorillonite is not introduced. The water resistance and thermal stability of the epoxy resin microcapsule wall material, i.e., urea-formaldehyde resin, decrease, so after water immersion and high heat treatment, the healing rate of the waterproofing membrane decreases. Comparison between Example 9 and Comparative Example 4 shows that, without introducing sorbate groups into styrene-butadiene rubber, only introducing DOPO, the antibacterial property of the modified styrene-butadiene rubber is greatly reduced, resulting in a greater weakening of the antibacterial property of the waterproofing membrane. Comparison between Example 9 and Comparative Example 5 shows that, without introducing DOPO into styrene-butadiene rubber, only introducing sorbate groups, the flame retardancy of the modified styrene-butadiene rubber is greatly reduced, resulting in a greater weakening of the flame retardancy of the waterproofing membrane.
[0108] The above contents are merely examples and explanations of the concept of the present invention. The technicians in this technical field may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the concept of the invention or exceed the scope defined by the claims, they should all fall within the protection scope of the present invention.
Claims
1. A self-adhesive polymer modified asphalt composite anti-root waterproofing membrane, characterized in that: It includes an isolation membrane layer, a polymer modified asphalt layer, a tread base layer, a polymer modified asphalt layer, and an isolation membrane layer arranged in sequence from top to bottom; the polymer modified asphalt layer includes the following raw materials in parts by weight: 48-52 parts of petroleum asphalt, 12-14 parts of aromatic oil, 3-5 parts of SBS, 13-15 parts of modified styrene-butadiene rubber, 5-7 parts of polyisobutylene, 4-6 parts of modified microcapsules, 1-2 parts of root inhibitor, 11-13 parts of light calcium carbonate, and 0.3-0.5 parts of silane coupling agent; The modified microcapsules are prepared by the following steps: Step A1: After the epoxy resin microcapsules are dried, the silane coupling agent 1 is hydrolyzed to modify the dried microcapsules to obtain amino-containing microcapsules; Step A2: adding 4-dimethylaminobenzoic acid and 6-chloro-1-hexene to n-propanol, stirring and reacting to obtain a quaternary ammonium salt product; The quaternary ammonium salt product, distilled water and ethanol are stirred and mixed, and then the nano-montmorillonite is added and stirred to obtain modified montmorillonite; Step A3: adding modified montmorillonite to DMF, then adding thionyl chloride, stirring to react to obtain an acyl chloride product; stirring to mix amino-containing microcapsules, potassium carbonate and dimethyl sulfoxide to obtain a mixed solution 1, then adding the acyl chloride product to dimethyl sulfoxide, stirring to mix to obtain a mixed solution 2, and dripping the mixed solution 2 into the mixed solution 1 under an ice-water bath, stirring to react to obtain an amide product; Step A4: stirring the amide product, 2,6-bis(tert-butyl)-4-(mercaptomethyl)phenol, DMF, and 4-dimethylaminopyridine under ultraviolet light to obtain modified microcapsules; The modified styrene-butadiene rubber is prepared by the following steps: Step B1: adding styrene butadiene rubber to cyclohexane and stirring for 30-40 minutes to obtain a styrene butadiene rubber solution; then adding meta-chloroperbenzoic acid to tetrahydrofuran and stirring for 10-15 minutes to obtain a meta-chloroperbenzoic acid solution; Then the styrene-butadiene rubber solution is heated to 35-40° C., and then the m-chloroperbenzoic acid solution is added dropwise to the styrene-butadiene rubber solution through a constant pressure dropping funnel. After the addition is completed, the mixture is stirred for 1.5-2.0 hours. A sodium hydroxide solution is added and stirred to separate the aqueous phase until the pH of the organic phase is 7-8. The organic phase is flocculated three times with anhydrous ethanol and tetrahydrofuran respectively, and then dried to obtain the epoxidized emulsion polystyrene-butadiene rubber. Step B2: Stirring and mixing the epoxidized emulsion polystyrene-butadiene rubber and DOPO, heating to 85-90°C, stirring for 10-15 minutes, adding triphenylphosphine, and heating to 140-150°C, maintaining for 3.5-4 hours to obtain a reaction solution, cooling the reaction solution to room temperature, adding ethyl acetate, standing for 48-50 hours, and filtering to obtain a hydroxyl product; Step B3: The hydroxyl product, pyridine, triethylamine and dimethyl sulfoxide are stirred and mixed to obtain a mixed solution a; sorbyl chloride is added to dimethyl sulfoxide to obtain a mixed solution b, and the mixed solution b is added dropwise to the mixed solution a in an ice water bath. After the addition is completed, the temperature is raised to 40-45° C., and the reaction is stirred at a constant temperature for 8-10 hours, and then the temperature is raised to 100-110° C., and stirring is continued for 1-2 hours. The modified styrene-butadiene rubber is obtained by distillation under reduced pressure.
2. The self-adhesive polymer modified asphalt composite anti-root waterproofing membrane according to claim 1, characterized in that: The isolation film layer is a polyethylene film layer, the tire base layer is a HDPE film layer; the root inhibitor is m-chloropropiophenone, the polyisobutylene is a highly active polyisobutylene, and the silane coupling agent is 10-alkenyl undecyl trimethoxy silane.
3. The self-adhesive polymer modified asphalt composite anti-root waterproofing membrane according to claim 1, characterized in that: In step A1, the usage ratio of silane coupling agent 1, deionized water and dried microcapsules is 5-6 g: 100-110 mL: 10-12 g; in step A4, the usage ratio of amide product, 2,6-bis(tert-butyl)-4-(mercaptomethyl)phenol, DMF and 4-dimethylaminopyridine is 5-6 g: 13-14 g: 80-90 mL: 0.5-0.7 g, and the power of ultraviolet light is 100-150 W.
4. The self-adhesive polymer modified asphalt composite anti-root waterproofing membrane according to claim 1, characterized in that: In step A2, the usage ratio of 4-dimethylaminobenzoic acid, 6-chloro-1-hexene and n-propanol is 0.1 mol: 0.1-0.13 mol: 65-75 mL; the usage ratio of quaternary ammonium salt product, nano-montmorillonite, distilled water and ethanol is 2.8-3.3 g: 1 g: 20-30 mL: 20-30 mL, and the volume fraction of ethanol is 95%.
5. The self-adhesive polymer modified asphalt composite anti-root waterproofing membrane according to claim 1, characterized in that: In step A3, the usage ratio of modified montmorillonite, DMF and dichlorothionyl is 5-6 g: 25-35 mL: 0.5-0.7 mol; the usage ratio of amino-containing microcapsules, potassium carbonate and dimethyl sulfoxide is 6-7 g: 0.3-0.5 mol: 55-65 mL; the usage ratio of acyl chloride product and dimethyl sulfoxide is 8-10 g: 45-55 mL; the usage ratio of mixed solution 1 and mixed solution 2 is 70-80 mL: 60-70 mL.
6. The self-adhesive polymer modified asphalt composite anti-root waterproofing membrane according to claim 1, characterized in that: In step B1, the usage ratio of styrene-butadiene rubber and cyclohexane is 10-15 g: 100-150 mL; the usage ratio of meta-chloroperbenzoic acid and tetrahydrofuran is 34.5-35.5 g: 100-110 mL; the usage ratio of styrene-butadiene rubber solution and meta-chloroperbenzoic acid solution is 110-120 mL: 12-14 mL; and the mass fraction of the sodium hydroxide solution is 10-15%.
7. The self-adhesive polymer modified asphalt composite anti-root waterproofing membrane according to claim 1, characterized in that: In step B2, the usage ratio of epoxidized emulsion polybutadiene styrene rubber, DOPO, triphenylphosphine and ethyl acetate is 21-23 g: 15-17 g: 0.05-0.07 mol: 150-160 mL.
8. The self-adhesive polymer modified asphalt composite anti-root waterproofing membrane according to claim 1, characterized in that: In step B3, the usage ratio of the hydroxyl product, pyridine, triethylamine and dimethyl sulfoxide is 26-28 g: 18-20 mL: 30-35 mL: 100-110 mL; the usage ratio of sorbyl chloride and dimethyl sulfoxide is 15-17 g: 40-50 mL; the usage ratio of mixed solution a and mixed solution b is 17-19 mL: 6-8 mL.
9. A method for preparing the self-adhesive polymer modified asphalt composite anti-root waterproofing membrane according to any one of claims 1 to 8, characterized in that: The steps include: Step S1: firstly, heating the petroleum asphalt to 200-210° C. under stirring, then adding aromatic oil, SBS, and modified styrene-butadiene rubber and continuing stirring for 1.5-2.0 hours, cooling to 90-100° C., then adding polyisobutylene, modified microcapsules, light calcium carbonate, and silane coupling agent and stirring for 1-1.5 hours, and finally adding a root inhibitor and stirring for 0.5-1.0 hours to obtain a polymer modified asphalt mixture; Step S2: coating the polymer modified asphalt mixture on the upper and lower surfaces of the tread base to form two upper and lower polymer modified asphalt layers, and then covering the outer surfaces of the upper and lower polymer modified asphalt layers with a polyethylene film to form two isolation film layers to obtain a self-adhesive polymer modified asphalt composite anti-root waterproof membrane; the thickness of the two polymer modified asphalt layers is the same and is both 3-5 mm.
Citation Information
Patent Citations
Self-glued asphalt adhesive material, preparation method of self-glued asphalt adhesive material, and self-glued asphalt waterproof coiled material
CN106398244A
Flame-retardant type modified bituminous waterproof sheet material and production method thereof
CN108049507A